Molecular features of tumor-derived genetic alterations in circulating cell-free DNA in virtue of autopsy analysis - Hayato Koba; Hideharu Kimura; Taro Yoneda; Takashi Sone; Noriyuki Ohkura; Johsuke Hara; Kazuyoshi Hosomichi; Atsushi Tajima; Kazuo Kasahara (Scientific Reports, 2021)
Abstract In cancer patients, circulating cell-free DNA (cfDNA) includes tumor-derived DNA (tDNA). cfDNA has been used clinically for non-invasive gene mutation testing. The aim of this study was to characterize the features of the genetic alterations detected in cfDNA. This study included 6 patients with primary lung cancer who died due to cancer progression. Tumors were biopsied at autopsy. Genetic alteration profiles were obtained using next generation sequencing. The features of the tDNA genetic alterations detected in cfDNA included a higher frequency of being present in multiple tumors (67% truncal mutations, 36% shared mutations, and 4% individual mutations) and a higher variant allele frequency (VAF; 47.6% versus 4.1% for tDNA alterations detected in cfDNA versus not detected in cfDNA, respectively). The data revealed that the tumor-derived genetic alterations most easily detected in cfDNA were truncal mutations with a high VAF. These results showed that essential genetic alterations enriched in cfDNA could help to characterize cancer cells and that genetic testing using cfDNA has advantages in the detection of fundamental regulatory aberrations occurring during tumorigenesis.